Cotas Raciais Ou Sistema Universal: Um Estudo Sobre O Acesso De Estudantes Negros(As) Na Universidade Federal De São Paulo - Oliveira, Sidney De Paula [UNIFESP] (2018)
In Brazil The Regulatory Norms, Mainly The Ones That Came Before The Federal Law N.º 12.711/12, Which Was Responsible To Regulate The Access To Universities And To Educational Institutes Through Racial Quotas Played A Key Part When It Comes To The Access Of Young People To Public Univertsities. In A Historic Moment In Which The Affirmative Actions Have Been Adopted By The Public Universities This Subject Matter Becomes Relevant And According To The Gradual Process Of Implementation These Kind Of Policies Are Subjected To Constantly Assessment About The Necessity/Feasibility Of Its Permanence Or Not. To This End, This Research Aims To Investigate The Possible Reasons Why Negro Students Choose To Get Into The Universtity Through The Usual Manner Instead Of Using The Specific Vacancies/Quotas Which They Are Allowed To, Due To Their Condition Of Taking Part Of That Group. The Methodology Of Data Collection Will Embrace Document Analysis And Interview With Six Negro Students Of Both Genders Who Are Currently Regis